The Project-based Learning Model using Design Thinking for the Innovators in the 21st Century - Sisamud, Kiattisak; ฉัตรวัฒนา, พินันทา (Journal of Technical and Engineering Education, 2023)
The objective of this research is to develop and study the results of the development of the project-based learning model using design thinking for the innovators in the 21st century. The sample group in the research, derived from purposive, includes five experts in the design and development of instruction models and instruction systems from various institutions in higher education. The results showed that 1) the project-based learning model using design thinking for the innovators in the 21st century consists of five steps: (1) preparation (2) topic definition (3) creation and test (4) presentation, and (5) evaluation, 2) The results of suitability assessment of the project-based learning model using design thinking showed that (2.1) the suitability of the project-based learning model using design thinking (overall elements) is at the highest level (mean=4.64, S.D.=0.54), (2.2) the suitability of the project-based learning model using design thinking (separate elements) is at the highest level (mean=4.56, S.D.=0.56), (2.3) the assessment of the project-based instruction process using design thinking is at the highest level (mean=4.58,S.D.=0.51), and (2.4) the suitability of the project-based learning using design thinking model (application) is at the highest level (mean=4.75, S.D.=0.36). In conclusion, the project-based learning model using design thinking can be used as guidelines in learning management to promote creative thinking skills for the innovators in the 21st century.